Free Chlorine and Peroxynitrite Alter the Capsid Structure of Human Norovirus GII.4 and Its Capacity to Bind Histo-Blood Group Antigens - Chassaing, Manon; Bastin, Guillaume; Robin, Maëlle; Majou, Didier; Belliot, Gaël; de Rougemont, Alexis; Boudaud, Nicolas; Gantzer, Christophe (Frontiers in Microbiology, 2021)
Human noroviruses (HuNoVs) are one of the leading causes of acute gastroenteritis worldwide. HuNoVs are frequently detected in water and foodstuffs. Free chlorine and peroxynitrite (ONOO−) are two oxidants commonly encountered by HuNoVs in humans or in the environment during their natural life cycle. In this study, we defined the effects of these two oxidants on GII.4 HuNoVs and GII.4 virus-like particles (VLPs). The impact on the capsid structure, the major capsid protein VP1 and the ability of the viral capsid to bind to histo-blood group antigens (HBGAs) following oxidative treatments were analyzed. HBGAs are attachment factors that promote HuNoV infection in human hosts. Overall, our results indicate that free chlorine acts on regions involved in the stabilization of VP1 dimers in VLPs and affects their ability to bind to HBGAs. These effects were confirmed in purified HuNoVs. Some VP1 cross-links also take place after free chlorine treatment, albeit to a lesser extent. Not only ONOO− mainly produced VP1 cross-links but can also dissociate VLPs depending on the concentration applied. Nevertheless, ONOO− has less effect on HuNoV particles.